“I feel [so alone] nothing” – emotional vulnerability and detachment as transdiagnostic key characteristics of patients with chronic tinnitus: a schema mode model approach - Boecking, Benjamin; Brueggemann, Petra; Mazurek, Birgit (Frontiers in Psychiatry, 2024)
Background Gold-standard approaches for chronic tinnitus involve hearing amplification measures and psychological therapy, where applicable. Whilst schema therapy is accumulating evidence as a transdiagnostically useful treatment framework, its applicability for patients with chronic tinnitus has not yet been examined. The present study (a) explores latent dimensions of psychological distress in a sample of chronic tinnitus patients, and (b) examines whether the schema mode model might explain these dimensions – thus constituting a potentially helpful conceptualization and treatment framework. Methods N = 696 patients with chronic tinnitus completed the Tinnitus Questionnaire, Tinnitus Handicap Inventory, Hospital Anxiety and Depression Scale, Perceived Stress Questionnaire and ICD-10 Symptom Rating. As criterion, patients further completed the Schema Mode Inventory (SMI-r) – which assesses psychological constructs linked to negative self-beliefs (“parent modes”), primary emotions resulting from unmet psychological needs (“child modes”), and secondary emotional or behavioral attempts to reinstate or maintain psychological equilibrium (“coping modes”). A varimax-rotated principal axis factor analysis grouped the primary item pool. Factor scale scores were then correlated with the SMI-r. Results A three-factor solution explained 37.4% of variance and represented 78% of the included items. Following item content examination, the factors represented (1) General emotional distress, (2) Tinnitus-attributed emotional distress, and (3) Socio-audiological impairment. Factors 1|2 correlated highly (r = 0.70), Factors 2|3 moderately (r = 0.62). Linked to the schema mode model, Factor 1 correlated highly with the “vulnerable child” (r = 0.78), and moderately with the “parent”, “angry child”, and “detached protector” modes (0.53 < r < 0.65). Factor 2 correlated moderately with the “vulnerable child” (r = 0.53). Factor 3 was largely uncorrelated with SMI-r scores – although a low correlation with the “detached protector” warrants further examination. Conclusion “General” and “tinnitus-attributed” emotional distress correlate highly – warranting holistic (not symptom-specific) psychological case conceptualization and treatment planning. Viewed from a schema mode perspective, the “vulnerable child” explains substantial variance across both dimensions. Consequently, autobiographically anchored, unmet emotional needs and emotional detachment constitute key treatment targets. Social-audiological impairment should be multimodally conceptualised and treated with hearing aids and psychological support measures, as applicable.